Acalculous Cholecystitis Prevalence on Abdominal Ultrasonography Examination of HIV/HCV Co-infection Patients in Cipto Mangunkusumo Hospital - Bambang Sutopo; Unggul Budihusodo; Irsan Hasan; Rino Alvani Gani; Evy Yunihastuti (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: Acalculous cholecystitis is commonly found in patients with human immunodeficiency virus (HIV) compared to general population. Surprisingly, the signs and symptoms are unremarkable. On the other hand, HIV/hepatitis C virus (HCV) co-infection is a common finding. The aim of this study was to evaluate whether HCV infection has any influence to HIV patients concerning acalculous cholecystitis prevalence. Method: A cross-sectional study was performed in HIV/HCV patients who visited AIDS study group clinic at Cipto Mangunkusumo hospital during September 2008 to February 2009. The patients who met the criteria were examined physically and underwent abdominal ultrasonography. Routine blood count, alanine aminotranferase, aspartate aminotransferase, cluster of differentiation 4 (CD4) and serum albumin were recorded. Results: Of 63 patients underwent ultrasonography examination, we found acalculous cholecystitis in 33 patients (52.3%), cholelithiasis and cholecystitis in 2 patients, and 28 patients were considered normal. Patients with CD4 less than 200 cells, tend to have acalculous cholecystitis more than those who had CD4 more than 200 cells. Conclusion: The prevalence of acalculous cholecystitis among HIV/HCV co-infection is higher compared to those with HIV infection alone. Keywords: acalculous cholecystitis, HIV/HCV co-infection, CD4